2003
DOI: 10.1121/1.1570438
|View full text |Cite
|
Sign up to set email alerts
|

Temporary threshold shifts and recovery following noise exposure in the Atlantic bottlenosed dolphin (Tursiops truncatus)

Abstract: Behaviorally determined hearing thresholds for a 7.5-kHz tone for an Atlantic bottlenosed dolphin (Tursiops truncatus) were obtained following exposure to fatiguing low-frequency octave band noise. The fatiguing stimulus ranged from 4 to 11 kHz and was gradually increased in intensity to 179 dB re 1 microPa and in duration to 55 min. Exposures occurred no more frequently than once per week. Measured temporary threshold shifts averaged 11 dB. Threshold determination took at least 20 min. Recovery was examined 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 16 publications
2
38
0
1
Order By: Relevance
“…Similar results were obtained in a study of the harbor porpoise, Phocoena phocoena, which demonstrated that attaining the relatively low TTS criterion of 6dB required short, low-frequency sound pulses of a seismic airgun of at least 200dBre.1μPa (Lucke et al, 2009). Conversely, a lower (179dBre.1μPa) but longer (30-50min) exposure of low-frequency (4 to 11kHz) fatiguing noise resulted in definite TTS (up to 11dB) in T. truncatus (Nachtigall et al, 2003).…”
Section: Fatiguing Sound Level and Durationmentioning
confidence: 99%
“…Similar results were obtained in a study of the harbor porpoise, Phocoena phocoena, which demonstrated that attaining the relatively low TTS criterion of 6dB required short, low-frequency sound pulses of a seismic airgun of at least 200dBre.1μPa (Lucke et al, 2009). Conversely, a lower (179dBre.1μPa) but longer (30-50min) exposure of low-frequency (4 to 11kHz) fatiguing noise resulted in definite TTS (up to 11dB) in T. truncatus (Nachtigall et al, 2003).…”
Section: Fatiguing Sound Level and Durationmentioning
confidence: 99%
“…In a study by Nachtigall et al (Nachtigall et al, 2003), a 50 min bandpass (4 to 11 kHz) noise exposure of 179 dB re. 1 μPa (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitive and wide-ranging hearing of toothed whales and dolphins, which is used for both passive hearing and echolocation (Au, 1993;Nachtigall et al, 2000), may be particularly susceptible to damage by intensive noise. The impact of noise on this auditory system is known as the permanent or temporary threshold shift (PTS or TTS, respectively), which is a reduction in sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, we do not know the noise exposure history of the present subject, but based on the location of the animal's stranding and its home range observed between 1996 and 2010, it is possible that the older dolphin had been exposed to chronic environmental noise from boating and shipping and other natural and anthropogenic sources of noise. However, controlled experiments with odontocetes have shown that high levels of exposure are needed to induce temporary threshold shifts (Finneran et al, 2002;Finneran et al, 2005a;Nachtigall et al, 2003;Mooney et al, 2009). During the post-stranding treatment and rehabilitation, the older dolphin was not given ototoxic medicines such as aminoglycosidic antibiotics, which might damage the hair cells of the cochlea and result in dolphin hearing loss (Finneran et al, 2005b).…”
Section: Discussionmentioning
confidence: 99%